A novel siglec (CgSiglec-1) from the Pacific oyster (Crassostrea gigas) with broad recognition spectrum and inhibitory activity to apoptosis, phagocytosis and cytokine release. (August 2016) - Liu, Conghui; Jiang, Shuai; Wang, Mengqiang; Wang, Lingling; Chen, Hao; Xu, Jiachao; Lv, Zhao; Song, Linsheng
Abstract: Sialic acid binding immunoglobulin-type lectin (siglec) belongs to the immunoglobulin superfamily (IgSF), which acts as regulator involved in glycan recognition and signal transduction in the immune and nervous systems. In the present study, a siglec gene (designated CgSiglec-1) was characterized from the Pacific oyster, Crassostrea gigas . The cDNA of CgSiglec-1 was of 1251 bp encoding a predicted polypeptide of 416 amino acids. CgSiglec-1 was composed of two I-set immunoglobulin (Ig) domains, one transmembrane (TM) domain and two ITIM motifs, sharing a sequence similarity with vertebrate CD22 homologs. The mRNA expression of CgSiglec-1 could be detected in all the selected tissues, with the highest level in hemocytes and labial palps. The confocal analysis revealed that CgSiglec-1 mainly distributed on the cytoplasmic membrane of the oyster hemocytes. In addition, the mRNA transcripts of CgSiglec-1 in hemocytes increased significantly (4.29-fold to that of control group, p  < 0.05) after Vibrio splendidus stimulation. The recombinant CgSiglec-1 protein (rCgSiglec-1) could bind to poly sialic acid (pSIAS), lipopolysaccharides (LPS) and peptidoglycan (PGN) in a dose-dependent manner. The blockade of CgSiglec-1 by specific polyclonal antibodies could enhance the LPS-induced cell apoptosis, phagocytosis towards V. splendidus and the release of cytokines, such as CgTNF-1, CgIFNLP and CgIL-17. The results collectively indicated that CgSiglec-1 could act as a bridge molecule between invader recognition and signal transduction cascade, and modulate the immune response by inhibiting various important processes of immunity in oyster. Highlights: A homolog of siglec with two I-set Ig domains and ITIM motifs was identified in Crassostrea gigas. It's mRNA was detected in all the tested tissues and its protein distributed at the cytoplasma membrane. Its mRNA expression in hemocytes was up-regulated after Vibrio splendidus challenge. The recombinant CgSiglec-1 exhibited a wide binding spectrum to PAMPs. It could modulate the apoptosis, phagocytosis and the release of cytokines.